Clinicopathological Features of 15 Occult and 178 Clinical Pancreatic Ductal Adenocarcinomas in 8339 Autopsied Elderly Patients. Issue 2 (February 2016) - Matsuda, Yoko; Ishiwata, Toshiyuki; Yachida, Shinichi; Suzuki, Akemi; Hamashima, Yuri; Hamayasu, Hideki; Yoshimura, Hisashi; Honma, Naoko; Aida, Junko; Takubo, Kaiyo; Arai, Tomio
Abstract : Objective: The aim of the study was to investigate the clinicopathological features of pancreatic cancer at different stages using autopsy results. Methods: We retrospectively evaluated 8399 consecutive cases of autopsy performed between 1972 and 2013 at our geriatric hospital. Results: Macroscopic pancreatic lesions were detected in 6.13% of the cases. Primary and secondary pancreatic tumors were observed in 2.88% and 2.10% of the cases, respectively. Most primary tumors were invasive ductal adenocarcinomas (193 cases [2.31%]; mean patient age, 78.09 years) with a peak incidence at 50 to 59 years. Occult invasive ductal adenocarcinoma was discovered incidentally in 15 cases, with distant metastasis present in 26.67% of those. Microscopically, occult and advanced tumors exhibited similar characteristics such as hyalinized fibrous stroma, necrosis, invasion into vessels, peripancreatic fat tissues, and extrapancreatic nerve plexus. Mucin 1 and 2 immunohistochemical expression levels were also similar. Occult cancer incidence increased with age. Patients aged 85 years or older had shorter survival, a small tumor size, and a low incidence of lymph node metastasis. Approximately 8% of pancreatic invasive ductal adenocarcinomas progressed asymptomatically and were discovered incidentally at autopsy. Conclusions: Pancreatic cancers in elderly patients tend to progress asymptomatically, but once symptoms develop, they are more often fatal than those in younger patients. Abstract : Supplemental digital content is available in the text.